ANALISIS SISTEM ANTRIANBANK RAKYAT INDONESIA KK UNISMA SEBAGAI UPAYAPENINGKATAN EFISIENSI PELAYANAN - Muhammad Azmil Nazar; Nur Hajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTQueues we often encounter in everyday life. Someone is required to wait, basically waiting is an activity or activity that requires time and is usually less pleasant, especially if the queue is long and long in getting service. Every company makes its own method so that customers or customers don't wait too long. In terms of service, the queuing system is an important factor because it is one measure of the efficiency of a business service. The use of the queue model can help the management in designing the operational system in this case is the teller, so that the quality of the service becomes optimal.This study is intended to analyze the effectiveness of the theory and queuing model, as well as the efficiency of the service by using this theory. Data sources were obtained from direct observations at Bank Rakyat Indonesia (BRI) KK UNISMA. In this study using multiple line queue system analysis (M / M / S). the results of this study indicate that queuing system performance is less optimal because of the low level of facility utilization and low teller activity level. Keywords: Service efficiency, tellers, queuing theory, multiple paths (M/M/S)